ACOUSTIC EMISSION AND VELOCITIES ASSOCIATED WITH THE FORMATION OF COMPACTION BANDS IN SANDSTONE - Fortin J.; Guéguen Y.; Stanchits S.; Dresen G. (My University, 2006)
A series of laboratory experiments has been conducted in which three-dimensional (3-D) locations of acoustic emissions (AE) were recorded and used to analyze the development of compaction bands in Bleurswiller sandstone, which has a porosity of 25%. Results were obtained for saturated samples deformed under triaxial compression at three different confining pressures (60, 80, and 100 MPa), a pore pressure of 10 MPa, and room temperature. We recorded acoustic emissions, compressional and shear wave velocities, and porosity reduction under hydrostatic condition and under triaxial loading conditions at a constant axial strain rate. Our results show that seismic velocities and their amplitude increased during hydrostatic pressure build up and during initial axial loading. During shear-enhanced compaction, axial and radial velocities decreased progressively, indicating an increase of stress-induced damage in the rock. In experiments performed at confining pressures of 80 and 100 MPa during triaxial loading, acoustic emissions were localized in clusters. During progressive loading, AE clusters grow horizontally, perpendicular to the maximum principal stress direction, indicating formation of compaction bands throughout the specimens. Microstructural analysis of deformed specimens confirmed a spatial correspondence of AE clusters and compaction bands. For the experiment performed at a confining pressure of 60 MPa, AE locations and microstructural. observations show symmetric compaction bands inclined to the cyller axis of the specimen, in agreement with predictions from recent theoretical models. Copyright 2006 by the American Geophysical Union.